PROMS and Radiological Outcomes in Mobile Bearing Total Ankle Arthroplasty for Patients with Varus or Valgus Deformity - Jack Allport MBChB; Adam Bennett MRCS; Jayasree Ramaskandhan MSc, MPT, MCSP; Malik Siddique DO (Foot & Ankle Orthopaedics, 2018)
Category: Ankle Arthritis Introduction/Purpose: There is increasing evidence that outcomes for total ankle arthroplasty (TAA) are not adversely affected by pre-operative varus deformity. There is a sparsity of evidence relating to outcomes in valgus ankle arthritis. We present our outcomes using a mobile bearing prosthesis (Mobility TAA system, DePuy, Raynham, Massachusetts, USA) with a comparison of neutral, varus and valgus ankles. Methods: This is a single surgeon, retrospective cohort study of consecutive cases. Cases were identified from a locally held joint registry which routinely records PROMS data pre-operatively and at annual intervals. Patients undergoing primary TAA between March 2006 and June 2014 were included. Rrevision procedures along with those with inadequate radiographic images for deformity analysis were excluded. Patients with inadequate PROMS data were included in the radiological analysis but not the PROMS analysis. Data collected included FAOS (Womac Pain, Function and Stiffness), SF-36 scores and patient satisfaction. Radiological data was gathered from routinely taken AP weight bearing radiographs pre-operatively, immediately post-operatively and at final follow up. Pre-operative deformity was measured between the tibial anatomical axis and a line perpendicular to the talus. Patients were classified as neutral, varus (≥10 degrees varus) or valgus (≥10 degrees valgus). Results: 230 cases (see image) underwent radiological classification (152 neutral, 60 varus, 18 valgus) and were included in the radiological analysis (mean follow-up 55.9 months). 164 cases were included in the PROMS analysis (mean follow-up 61.6 months). The groups were similar with regards to BMI and length of follow-up but neutral ankles were younger (P<0.001). Baseline scores were equal except physical health with valgus ankles scoring lowest (P=0.045). Valgus ankles had statistically better post-operative pain (P=0.0247) and function (P=0.012) than neutral ankles. Pre to post-operative change did not reach statistical significance except physical health where valgus outperformed neutral and varus (p=0.039). Mean post-operative angle was 3.1 and final angle 3.7 with no significant differences. There was no significant differences in revision rates. Conclusion: Our study confirms previous evidence that varus deformity does not affect outcome in TAA. Contrary to this, valgus ankles in our cohort performed better post-operatively than neutral ankles. Post-operative coronal radiological alignment was not affected by pre-operative deformity and was maintained over a number of years. Coronal plane deformity does not negatively impact either radiological or clinical outcomes in TAA should not be considered an absolute contra-indication.